2015
DOI: 10.1016/j.joa.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Successful transjugular extraction of a lead in front of the anterior scalene muscle by using snare technique

Abstract: a b s t r a c tThe incidence of cardiovascular implantable electronic device infection is increasing. We report a case of and successful device removal in a 79-year-old man with implantable cardioverter-defibrillator infection. Right phrenic nerve paralysis was evident on chest radiography. The lead was in front of the anterior scalene muscle, close to the left phrenic nerve. Therefore, extraction carried a risk of bilateral phrenic nerve paralysis. The lead was successfully extracted from the right internal j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…There have only been a few reports of lead extraction, particularly in Japan [14][15][16]. In the present study, we showed that extraction of CIEDs in a series of 29 patients with 61 leads was clinically expedient and successful.…”
Section: Discussionsupporting
confidence: 59%
“…There have only been a few reports of lead extraction, particularly in Japan [14][15][16]. In the present study, we showed that extraction of CIEDs in a series of 29 patients with 61 leads was clinically expedient and successful.…”
Section: Discussionsupporting
confidence: 59%
“…Okamura et al [2] reported their initial 40 cases. Ohmori et al [3] reported a case of a thoracoscopy-guided lead extraction with an excimer laser sheath and Okada et al [4] reported a case of a transjugular extraction using a snare technique. Our current study consisted of 183 patients, the largest cohort in Japan, and, therefore, this study can clarify the status of device infections and lead extractions in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…We introduced the excimer laser system in 2009 for the transvenous removal of the implanted leads. However, there have been few reports [2] , [3] , [4] concerning the management of cardiac device infections. The purpose of this study was to review our single center experience and to clarify the current status of cardiac implantable electronic device (CIED) infections in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…money to replace the entire pacemaker system (lead + battery). 11, 12 We used the conventional technique by moving the pacemaker bag further away. medially treated with intravenous antibiotics for 14 days.…”
Section: Case Reportmentioning
confidence: 99%